Entrevista em serviço social: uma rediscussão crítica do instrumento técnico-operativo - RODRIGUES, Samara Morais (Universidade Federal do Pará, 2015)
The interview instrument understood as a mediator in the process of knowledge, enables the social worker approaches the reality of their demand, transcending the appearance of phenomenon and getting larger interventional possibilities on the expressions of the social question. Based on this understanding, this dissertation analyze, critically, as has been given to contemporary professional practice of social work, specifically the use of the instrument interview. for this purpose the different theoretical and methodological conceptions about the interview were identified in the social sciences and the debate on the relationship between theory and practice in social work, as well as, was analyzed the understanding about how to use the interview by social workers in professional practice. Guided by dialectical critical method, the argument came from analyzes of theoretical support materials and of a field research with interviews with two social workers active in the social assistance and two in theHealth. As a result identified that the lack of larger problematizations about the instrument has repercussions in the institutional context, the majority of the interviewees had difficulty associating the instrument with theoretical references and, not identified the interview as an instrument of mediation, suggesting that the dichotomy between theory and practice is very present in professional practice of social worker.